2010
DOI: 10.1149/1.3308596
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of CO[sub 2] to CO by Electrolysis of Molten Lithium Carbonate

Abstract: The conversion of CO2 to CO by electrolysis of molten Li2CO3 was investigated. Using a cell comprising a Ti cathode, a graphite anode and a source of CO2 allows the continuous electrolysis of the melt at 900°C with current densities at the electrodes higher than 100mA/cm2 . The faradaic efficiency of the process is close to 100%, and the thermodynamic efficiency at 100mA/cm2 is 85% . The proposed method has several advantages: (i) No precious metal is required, (ii) no hazardous or toxic by-product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
142
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 21 publications
0
142
0
Order By: Relevance
“…• C. Kaplan et al [3][4] observed the conversion of CO 2 to CO by using a cell with a molten electrolyte consisting of lithium carbonate and lithium oxide, in which the electrodes were graphite (anode) and titanium (cathode), and the working temperature was 850-900…”
mentioning
confidence: 99%
“…• C. Kaplan et al [3][4] observed the conversion of CO 2 to CO by using a cell with a molten electrolyte consisting of lithium carbonate and lithium oxide, in which the electrodes were graphite (anode) and titanium (cathode), and the working temperature was 850-900…”
mentioning
confidence: 99%
“…The possibility of electrolysis in molten carbonate salts has been evidenced [15][16][17][18][19], but was initially investigated for carbon dioxide capture by converting CO2 into CO and/or C. Peelen et al [15] studied the electrochemical reduction of CO2 into CO on a gold flag electrode in Li/K carbonate eutectics at temperatures from 575 to 700 °C. Kaplan et al [16,17] studied the conversion of CO2 to CO in a cell operated at 850-900 °C.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Some researchers have investigated the conversion of CO 2 into carbon or carbon monoxide by electrolysis in a molten salt. 8,[10][11][12][13] Carbon deposition has typically been achieved through the formation of carbon powders or carbon film.…”
Section: Introductionmentioning
confidence: 99%